2012
DOI: 10.2217/npy.12.40
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and neuropsychological findings in pediatric obsessive–compulsive disorder: a review and developmental considerations

Abstract: Pediatric obsessive-compulsive disorder (OCD) appears to be distinct from its adult counterpart, especially in preadolescent patients.In contrast to the majority of adult imaging studies, a volumetric increase has been identified in the frontal and, in particular, striatal regions in pediatric OCD.Imaging research indicates increased frontostriatal metabolism in the pediatric OCD population, but decreased activation in preadolescent young children.The decreased activation correlates with OCD symptomatology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 152 publications
(187 reference statements)
3
22
0
Order By: Relevance
“…Due to the small body of neuropsychological research in pediatric OCD (for a review and meta analysis see Abramovitch et al, 2012b;Abramovitch et al, In-press), this review focuses on adult studies. A total of 207 published research articles were identified through February 2012.…”
Section: Systematic Literature Search and Selection Criteriamentioning
confidence: 99%
“…Due to the small body of neuropsychological research in pediatric OCD (for a review and meta analysis see Abramovitch et al, 2012b;Abramovitch et al, In-press), this review focuses on adult studies. A total of 207 published research articles were identified through February 2012.…”
Section: Systematic Literature Search and Selection Criteriamentioning
confidence: 99%
“…(For a review see Abramovitch et al, 2012b). In brief, early onset OCD may be characterized by abnormal neuronal maturational processes.…”
Section: Introductionmentioning
confidence: 99%
“…Impairments have also been observed in some studies of planning and decisionmaking, although other studies have failed to replicate these fi ndings (Menzies et al 2008 ). Other studies have found few or no impairments on a range of executive functioning tasks in individuals with OCD (Abramovitch et al 2012 ).…”
Section: Psychobiology Neuropsychologymentioning
confidence: 99%
“…Compared to healthy controls, adults with OCD tend to show reduced OFC volume (Menzies et al 2008 ;Rotge et al 2009 ) but increased glucose metabolism at rest (Harrison et al 2009 ) and in response to symptom-provocation paradigms, wherein OCD symptoms are elicited in the scanner (Rotge et al 2009 ). Notably, this hypermetabolism in the OFC and in several other regions is normalized following effective cognitive-behavioral therapy or pharmacotherapy for OCD (see Abramovitch et al 2012 for a review).…”
Section: Neurobiologymentioning
confidence: 99%
See 1 more Smart Citation